KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVIS BAWAH PERMAINAN BOLAVOLI TIM SMP NEGERI 9 PEKANBARU - Tri Kurniawan; Drs. Saripin, M.Kes, AIFO '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract,: The problem in this study was less maximal of under serviced ability. It is suspected because of the low explosive power muscle arms and shoulder. This study was conducted to determine whether there is a contribution among explosive power arms and shoulders with the under serviced ability in volleyball game at SMP N 9 Pekanbaru team. The sample in this study was Volleyball Team of SMPN 9 Pekanbaru amounts to 12 people. Sampling in this study using total sampling technique. Instruments used in this research was Two-Hand Medicine Ball Put test that aims to measure the explosive power muscle arms and shoulders and then the skills of under Serviced Tests which aims to measure the ability of service to direct the ball towards the right target and direction. After that, the data processed with statistical, to examine normality with lilifors test at significant level α0,05. The hypothesis is suspected that there is a significant contribution among the power of muscle arms and shoulders with the abillity of under serviced on volleyball game. Based on analysis of Lilifors test produce LCalculated (x) for 0.073 and Ltable 0.242, LCalculated (y) for 0.025 and Ltable 0.242, it means Lcalculated <Ltable, then the samples come from a normal distribution population. The results of analysis correlation between Explosive Power Muscle Arms (x) on the results of under serviced volleyball of SMPN 9 Pekanbaru was obtain rCalculated 0.120 < rTable 0.602, it means Ha was rejected and Ho was accepted. Thus there was no significant contribution between Explosive Power Muscle Arms with under serviced volleyball results in volleyball games at SMPN 9 Pekanbaru. With the contribution amounts to 1.44%.Key Words: Explosive Power Muscle Arms and Shoulder, Under Serviced Ability